KEBERADAAN TARI ASIK NITI NAIK MAHLIGAI DI DESA SIULAK MUKAI KECAMATAN SIULAK KABUPATEN KERINCI - Eke Febrianti; Afifah Asriati; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2013)
Abstract This article exposes and describes the existance of Asik Niti Mahligai dance in Siulak Mukai village, sub-regency Siulak, Kerinci Regency. It is a qualitative research by using descriptive method. Data were collected through interview, observation, and library study. Data were analyzed by using ethnography and phenomenology approach. This research finding showed that during 2001-2012, Asik Niti Naik Mahligai dance did not get enough supports from the government and the society, in term of using, maintaining, and conserving this dance. Besides, the conservation of Asik Niti Naik Mahligai dance was disturbed by lack of interest of the young generation especially girl. As the effect, the existence of Asik Niti Naik Mahligai dance is endangered to be vanished.